China's relations with Arab and Persian gulf countries ("Journal "U". Economy. Management. Finance.", 2023)
Over the past decade, China has significantly expanded its economic, political, and power presence in the Middle East, becoming the largest trading partner and external investor for many Arab and Gulf countries. China still does not seek to challenge the U.S.-led security architecture in the Middle East or play a significant role in regional politics. However, China's growing economic presence could lead to increased engagement with the region, which could significantly affect the interests of other countries. China's influence on regional stability and political dynamics is growing, especially with regard to sensitive issues such as surveillance technology and arms sales. Interested states need to look for opportunities to cooperate with China in the Middle East.
Keywords: Arab countries; Gulf states; regional politics; international relations; global studies